Wybrane modele analizy historii zdarzeń i ich zastosowania w badaniach preferencji - Bąk, Andrzej (Selected models of event history analysis and their applications in the research of preferences, 2006)
The main aim of the paper is presentation of the event history analysis models and its applications in the area of consumer preferences research. There are presented: - basic guidelines of the event history analysis, - possibilities of the use event history models in the consumer preferences analysis, - proportional hazard model application in the research of consumer preferences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 363-371